Perlindungan Wajib Pajak dalam Perspektif Administrasi Publik: Analisis Peran Ikatan Wajib Pajak Indonesia (IWPI) sebagai Representasi Kepentingan Publik - Rinto Setiyawan; Zetria Erma; Ismayani Ismayani; Novi Yanti (SENTRI: Jurnal Riset Ilmiah, 2026)
Taxation constitutes a primary instrument for financing government administration and public development. However, the relationship between the state and taxpayers is not always balanced. Tax authorities possess extensive powers in tax assessment, collection, and enforcement, while taxpayers often occupy a structurally weaker position. This imbalance creates conditions for administrative domination and potential abuse of authority. This article analyzes taxpayer protection from a public administration perspective by examining the role of the Indonesian Taxpayers Association (IWPI) as a form of public interest representation. The study adopts a conceptual review and policy analysis approach, utilizing documentary analysis of tax regulations, public administration literature, and IWPI’s institutional framework. The findings indicate that mechanisms for taxpayer representation are essential to strengthening accountability in tax administration and rebalancing power relations between the state and citizens. From a legal standpoint, IWPI faces no formal barriers, as it is established as a legally recognized association. However, its effectiveness is constrained by structural obstacles, particularly limited access to tax policymaking processes and information. These constraints are closely linked to the authoritarian character of Indonesia’s tax administration, where normative and technical authority is highly centralized under the Minister of Finance. This centralization is reflected in the extensive delegation of regulatory authority through ministerial regulations, as well as in the institutional positioning of the Directorate General of Taxes and the Tax Court, which remains administratively under the Ministry of Finance until 31 December 2026. The article argues that taxpayer protection is an integral component of democratic governance and underscores the need for institutional reform to reduce power asymmetries within tax administration.